Liquid AP‐UV‐MALDI Enables Stable Ion Yields of Multiply Charged Peptide and Protein Ions for Sensitive Analysis by Mass Spectrometry1. Issue 8 (22nd January 2013) - Cramer, Rainer; Pirkl, Alexander; Hillenkamp, Franz; Dreisewerd, Klaus
<x xml:space="preserve">Abstract</x> All charged up: High and prolonged yields of multiply charged peptide and protein ions can be formed in MALDI mass spectrometry using liquid UV‐MALDI matrices and a heated ion‐transfer tube. The key features are low laser energies of 1–10 μJ, resulting in fluences of less than 200 to 2000 J m−2 and low sample ablation, high sensitivity, and continuous ion generation over tens of thousands of laser shots.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>